Oracle application server web toolkit reference - Bradley D Brown (Osborne McGraw-Hill, 1998)
The book includes undocumented strategies for designing, building, implementing, and supporting Web applications. Sample scripts, taken from real-life examples. It also shows how to build effective applications in an Oracle RDBMS environment